No Evidence for Single-Copy Immune-Gene Specific Signals of Selection in Termites - Meusemann, Karen; Korb, Judith; Schughart, Maximilian; Staubach, Fabian (Frontiers in Ecology and Evolution, 2020)
Selection pressures from pathogens appear to play an important role in shaping social evolution. Social behavior, in particular brood care, is associated with pathogen pressure in wood-dwelling “lower” termites. Yet, generally pathogen pressure is predicted to be low in wood-dwelling termite species that never leave the nest except for the mating flight. In comparison, pathogen pressure is predicted to be higher in species that leave the nest to forage, and thus constantly encounter a diversity of microbes from their environment. We hypothesized that such differences in predicted pathogen pressure are also reflected by differences in the intensity of natural selection on immune genes. We tested this hypothesis in a phylogenetic framework, analyzing rates of non-synonymous and synonymous substitutions on single-copy immune genes. Therefore, we leveraged recent genomic and transcriptomic data from eight termite species, representing wood-dwelling and foraging species as well as 14 additional species spanning the winged insects (Pterygota). Our results provide no evidence for a role of pathogen pressure in selection intensity on single-copy immune genes. Instead, we found evidence for a genome-wide pattern of relaxed selection in termites.